(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Three pedons studied representing the Bhajanpur, Panchagarh and Ruhea of the Black Terai soils (Humic Dystrudepts) indicated that maximum genetic color development has taken in the upper zone due to significant contribution of organic matter. Sand was the dominant fraction with higher sand: silt ratio. The soils were acidic in nature with low C and N content and CEC. Ca2+ was the dominant cation where as Mg2+ was very scanty. Bulk mineralogical analysis showed that soils were enriched with quartz, muscovite or potash mica, orthoclase, illite and zeolite. J. Asiat. Soc. Bangladesh, Sci. 40(1): 61-65, June 2014